Developing fuzzy tool capability measurement system analysis - Ghane, Neda; Avakh Darestani, Soroush; Ismail, Md Yusof; Azam, Moradi Tadi (Qazvin Islamic Azad University, 2021)
Due to the existing competitive environment of global economy, many companies allocate their major financial and human resources to quality improvement. Since, using measurement tool is an essential component in quality analysis and highly depends on quality of measurement systems and their results; measurement systems applications after calibration are the most efficient methods in real operations. Thus, inherent changes of measurement tools can be studied by computing capability index of measurement tools. This paper aims to develop a fuzzy model for computing capability.Fuzzy model for computing capability (Cg،Cgk) with data in the form of fuzzy triangular and trapezoidal numbers using MATLAB is developed and then a case study applying proposed method is presented.Finally, we compare presented results with classical outcomes and prove that fuzzy environment gives more flexibility, rather than classical environment.